Policy Implementation of the Beasiswa Pendidikan Indonesia (BPI) Program by the Kementerian Pendidikan Kebudayaan Riset dan Teknologi (Kemdikbudristek) - Ulfatul Khoiriyah; Masduki Ahmad (research, training and philanthropy institution Natural Aceh, 2023)
The study in this research aims to determine the implementation of the Beasiswa Pendidikan Indonesia (BPI) program policy organized by the Kementerian Pendidikan Kebudayaan Riset dan Teknologi (Kemdikbudristek) with a series of research using descriptive-qualitative methods through interviews and documentation studies. The research targets were the Pusat Layanan Pembiayaan Pendidikan (Puslapdik) and teachers in Indonesia. From the research activities carried out, it was found that, in general, most people in this case (teachers and education personnel) were aware of the BPI program initiated by Kemdikbudristek. However, there are still some problems that must be of particular concern to Kemdikbudristek to be followed up to disseminate the advantages of the BPI program as a form of active steps to solve educational problems by providing the widest possible opportunity for teachers and education personnel to continue competence in certain scientific fields in order to develop academic and technical abilities in Higher Education through participation in the selection of the BPI program. Therefore, the government needs to make measurable efforts by conducting routine and consistent socialization activities in conducting a holistic public introduction to the BPI program through meetings with program implementers and including training for teachers and education personnel such as; partnering with the Education community in the society